Association between community-based resource collection site use and functional disability risk among older adults: A Quasi-experimental study - Noriyuki Abe; Kazushige Ide; Kenjiro Kawaguchi; Daisuke Kumazawa; Katsunori Kondo (PLoS ONE, 2025)
This study aimed to investigate the longitudinal association between users versus non-users of MEGURU STATION, a community-based resource collection site, and the risk of functional disability among older adults in Japan. This quasi-experimental study included 973 older adults aged ≥65 years from three communities in Japan. Baseline and follow-up surveys were conducted 1 year apart to measure the risk scores for functional disability (RSFD) as the primary outcome. The main explanatory measure was self-reported MEGURU STATION use, with participants categorized as users or non-users. Mixed-effects linear regression models accounted for community-level variability and were adjusted for covariates, including sex, age, activities of daily living (ADL), education, subjective economic status, residential status, employment, and social participation. An additional analysis examined changes in going out, social interaction, and participation in community activities associated with MEGURU STATION use. Of the participants, 19.2% reported MEGURU STATION use. MEGURU STATION use was associated with a lower RSFD (B = −1.20, 95% confidence interval: −2.27, −0.12). Users reported increased opportunities for social interaction, participation in community activities, and going out compared with non-users. In summary, MEGURU STATION, a community-based intervention that integrates social interaction into daily routines, lowers the risk of functional disability among older adults. This scalable and socially inclusive model holds promise for promoting healthy aging. Future research should investigate its long-term impact and cultural adaptability.